KORELASI PENYAKITVIRUS TUNGRO DENGAN BERBAGAI JENIS WERENG PADA TANAMAN PADI (Oryza sativa) Di JAWA TIMUR - Nirwanto, Herry; Hamid, Abdul (MAPETA, 2009)
ABSTRACTThe objective of research is to know the correlation between Tungro disease and various leafhopper at paddy crop in some sub-province East Java. Making ofepidemic model conducted by using obtained data of laboratory Perception of Pest and Disease of Crop Food and Horticulture and also Report Observer of Pest Disease . Data analysis was based on the intensity of tungro disease, the frequency of rainy day and rainfall per month, pattern of planting, population of green leafhopper, as well as competitor insect as natural enemy. Correlation and multiple regression analysis was used to make epidemic model. The results of this study indicated that epidemic model of tungro disease with linear regression was Y= 641.659 + 1.925 ( Rainfall + 17.815 (Green leafhopper)) + 30.014 ( Brown leafhopper) + 60.493 ( Zigzag leafhopper) - 59.444 ( spider) - 122.425 ( Rain day) ( R = 0.988). This model significantly can explain correlation between rainfall, rainy day, vector insect to the severity of tungro disease at paddy crop. Keyword: Model, Tungro disease, green leafhopper